2014
DOI: 10.1007/s00439-014-1519-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental components of family history in type 2 diabetes

Abstract: Family history of diabetes is a major risk factor for type 2 diabetes (T2D), but whether this association derives from shared genetic or environmental factors is unclear. To address this question, we developed a statistical framework that models four components of variance, including known and unknown genetic and environmental factors, using a liability threshold model. Focusing on parental history, we simulated case-control studies with two first-degree relatives for each individual, assuming 50% genetic simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Despite increasing evidence suggesting that T2D is associated with increased risk of colorectal cancer (2)(3)(4)(5), no previous study has investigated whether family history of diabetes, a strong risk factor for T2D, might be related to colorectal cancer. An estimation by a statistical liability threshold model suggests that shared genetics is responsible for 68% of the association between parental history and T2D, with the remainder due to shared environmental factors (6), which is consistent with reports from empirical epidemiologic studies (28,29). However, in the EPIC-InterAct study, adiposity, lifestyle, and a genetic risk score comprising 35 single-nucleotide polymorphisms associated with T2D only accounted for a small proportion of the risk increase related to family history of diabetes, leaving the majority of the risk unexplained, and the genetic risk score alone explained only 2% of the family history-associated T2D risk (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increasing evidence suggesting that T2D is associated with increased risk of colorectal cancer (2)(3)(4)(5), no previous study has investigated whether family history of diabetes, a strong risk factor for T2D, might be related to colorectal cancer. An estimation by a statistical liability threshold model suggests that shared genetics is responsible for 68% of the association between parental history and T2D, with the remainder due to shared environmental factors (6), which is consistent with reports from empirical epidemiologic studies (28,29). However, in the EPIC-InterAct study, adiposity, lifestyle, and a genetic risk score comprising 35 single-nucleotide polymorphisms associated with T2D only accounted for a small proportion of the risk increase related to family history of diabetes, leaving the majority of the risk unexplained, and the genetic risk score alone explained only 2% of the family history-associated T2D risk (9).…”
Section: Discussionmentioning
confidence: 99%
“…A family history of diabetes reflects both genetic background and shared environmental risk factors (6) and is a risk factor for a range of metabolic abnormalities (7) and development of T2D (8,9). Interestingly, an analysis in the EPIC-InterAct study showed that established lifestyle and genetic risk factors only explained a marginal proportion of the excess T2D risk associated with family history, highlighting the potential independence of family history as a risk factor (9).…”
Section: Introductionmentioning
confidence: 99%
“…Family history of diabetes is a reflection of both genetic components and environmental components, such as behavior and lifestyle (e.g., diet and exercise), that are shared, to some extent, by a family. Regarding genetic factors, recent advances in genetic technologies have revealed a growing number of genes that are related to type 2 diabetes; to date, >120 distinct genetic loci, with >150 variants, with potential involvement in the pathogenesis of type 2 diabetes have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the International Diabetes Federation (IDF) has reported that in 2013, 382 million human (8.3%) of the world's population suffered from diabetes that 175 million of them have not been diagnosed and has predicted that almost 592 million human (10.1%) will be affected to this disease by the year 2035 (IDF, 2011). This increasing process is assigned to the environmental and genetic factors (Das, 2010;Cornelis, Zaitlen, Hu, Kraft, & Price, 2015). Diabetes risk factors include low motility, obesity, genetics, race, age, hypertension, high triglycerides and low high density lipoproteins (HDL) (Katzmarzyk, 2008;Group, 2013).…”
Section: Introductionmentioning
confidence: 99%